Evaluation of the maladaptation of the test base in acrylic resin regarding the technique of preparation, place of measurement and storage time - Oliveira, Natália Pereira De; JÓias, Renata Pilli; Rossoni, Rodnei Dennis; JÓias, Renato Morales (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
AbstractIntroduction The most used material for the preparation of the baseplates is the acrylic resin, but it can present distortions.Objective To evaluate preparation technique, region and storage time that presents less maladaptation of the base when made with self-cured acrylic resin.Material and method Models were created in gypsum type III simulating edentulous maxilla, as divided into 3 groups (n = 10): GC (control group) thermopolymerizable acrylic resin; G1 - manual adaptation technique and G2 - drip technique. For the measurements, silicone by condensation of light consistency that was interposed between base and model was used. With a hydraulic press, 50 kg pressure was applied leading the base of the model. The obtained mold was measured in the palate, canine and molar regions with a digital caliper at the following times: immediately after the base polymerization, at 24, 48, 72, 96 hours and one week. The results were submitted to statistical analysis.Result G1 presented maladaptation of 0.43 mm ± 0.10, while G2 obtained 0.39 mm ± 0.11. The lowest maladaptation occurred in the CG. The palate region presented greater maladaptation (0.52 ± 0.07) and the canine region, the lowest (CD = 0.27 mm ± 0.07 and CE = 0.27 ± 0.09); There was no statistically significant difference for storage times.Conclusion G2 presented lower values than G1, with no statistically significant difference. The palate region presented greater maladaptation, followed by molars and canines. The bases continued to maladaptation the model after the immediate polymerization, with no statistically significant difference.

ResumoIntrodução O material mais empregado para confecção da base de prova é a resina acrílica por oferecer maior rapidez e praticidade, embora tenda a maior distorção.Objetivo Avaliar técnica de confecção, região e tempo de armazenagem que apresente menor desadaptação da base de prova confeccionada com resina acrílica ativada quimicamente.Material e método Confeccionaram-se modelos em gesso tipo III simulando maxila edêntula que foram divididos em 3 grupos (n = 10): GC - (grupo controle) resina acrílica termopolimerizável; G1 – técnica da adaptação manual; e G2 – técnica do gotejamento. Para as mensurações utilizou-se silicone por condensação de consistência leve que foi interposto entre base e modelo. Com uma prensa hidráulica aplicou-se pressão de 50 kg levando a base de encontro ao modelo. O molde obtido foi mensurado nas regiões de palato, caninos e molares com paquímetro digital nos seguintes tempos: imediatamente após a polimerização da base, em 24, 48, 72, 96 horas e uma semana. Os resultados foram submetidos à análise estatística.Resultado O G1 apresentou média de desadaptação de 0,43mm±0,10, enquanto o G2 obteve 0,39 mm ± 0,11. Os menores valores de desadaptação ocorreram no GC; A região do palato apresentou maior desadaptação (0,52 mm ± 0,07) e a região de caninos, as menores (CD = 0,27 mm ± 0,07 e CE = 0,27 ± 0,09); Não houve diferença estatisticamente significante para os tempos de armazenagem.Conclusão O G2 apresentou menores valores que o G1, sem diferença estatisticamente significante; A região de palato apresentou maior desadaptação, seguida de molares e caninos; As bases continuaram desadaptando ao modelo após a polimerização imediata, sem diferença estatisticamente significante.
Avaliação da desadaptação da base de prova em resina acrílica em relação à técnica de confecção, local de mensuração e tempo de armazenagem
Keywords: Acrylic resins; denture, complete; denture retention; dental materials; Resinas acrílicas; prótese total; retenção de dentadura; materiais dentários